2015
DOI: 10.1177/0093650214565925
|View full text |Cite
|
Sign up to set email alerts
|

Disadvantaged Minorities’ Use of the Internet to Expand Their Social Networks

Abstract: An essential argument of the social diversification hypothesis is that disadvantaged groups use the Internet rather than face-to-face communication to broaden social networks, whereas advantaged groups use the Internet to reinforce existing network ties. Previous research in this area has not accounted for both online and off-line communication, has only been examined with cross-sectional data, and has primarily been studied in Israel. To address these gaps with a U.S. data set, 2,669 conversations were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 43 publications
6
46
2
Order By: Relevance
“…Micheli (2016) indicated that low-income high-school students in Italy were more likely to engage in "horizontal" communicative and relational activities on SNSs with peers, while upper class youth were more concerned with "vertical" CE activities related to parental socialization. However, Gonzales (2017) found that racially or educationally disadvantaged individuals reported more online network expansion rather than maintenance. Such new, bridging, ties provide the greatest opportunities for reducing inequalities.…”
Section: Digital Divide and Snssmentioning
confidence: 85%
See 1 more Smart Citation
“…Micheli (2016) indicated that low-income high-school students in Italy were more likely to engage in "horizontal" communicative and relational activities on SNSs with peers, while upper class youth were more concerned with "vertical" CE activities related to parental socialization. However, Gonzales (2017) found that racially or educationally disadvantaged individuals reported more online network expansion rather than maintenance. Such new, bridging, ties provide the greatest opportunities for reducing inequalities.…”
Section: Digital Divide and Snssmentioning
confidence: 85%
“…The SNS divide in Armenia has implications for reducing opportunities for the bridging type of social capital development, which provides the greatest opportunities for reducing inequalities (Gonzales, 2017). As Liewrouw (2001) argues, the generation, circulation, and use of information in a society can create different information environments through fragmentation, with negative effects (Dahlberg, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Social media allow highthroughput networking and exploration of careers, which benefits trainees who may otherwise lack access to professional development (8) …”
Section: Jeremy Bergmentioning
confidence: 99%
“…Social media serve an important role in the movement toward increased equity, diversity, and inclusion within STEM because it provides a widely available, readily accessible platform for many to use easily. Social media allow highthroughput networking and exploration of careers, which benefits trainees who may otherwise lack access to professional development (8). Although not free from the bias and prejudice inherent in society, social media can connect diverse groups, enable rapid information exchange, and mobilize like-minded communities.…”
Section: 1126/science Aat7935mentioning
confidence: 99%